Taxonomy of the bee species Anthrenoides nigrinasis (Vachal, 1909) n. comb.: redescription of the type, description of the female, and new distribution records (Hymenoptera: Apoidea) - Ramos, Kelli S. (Zootaxa, 2018)
Protandrenini includes approximately 420 species of short-tongued bees, which are exclusively distributed in the Americas (Michener 2007; Moure et al. 2007; Ascher & Pickering 2017). Members of this tribe are mostly found in xeric and temperate areas in South America, and their diversity is still greatly underestimated. In fact, a major challenge to the systematics of Protandrenini is the outstanding number of species unplaced in genera or awaiting formal description (Ruz & Chiappa 2004; Ramos & Melo 2006; Michener 2007; Moure et al. 2007; Ramos & Rozen 2014). In addition to several taxa currently considered of uncertain position within the tribe, many South American genera are in need of taxonomic revision, such as Rhophitulus Ducke, Anthrenoides Ducke, and Psaenythia Gerstaecker (Silveira et al. 2002; Michener 2007; Ramos & Melo 2010; Moure et al. 2007).